Resilience and Psychological Well-Being Among Working Members of The Sandwich Generation in The Jabodetabek - Dianita Mar'atus Sholikhah; Rijal Abdillah; Yomima Viena Yuliana (Journal of Psychology and Social Sciences, 2026)
The sandwich generation refers to individuals who are responsible for meeting their own needs while simultaneously providing support to financially dependent family members. These multiple responsibilities may affect an individual's psychological well-being. One factor that is considered important in maintaining psychological well-being is resilience. This study aimed to examine the relationship between resilience and psychological well-being among working sandwich generation individuals in the Jabodetabek area. This study employed a quantitative approach with a correlational design. A total of 150 participants were recruited using a snowball sampling technique. Resilience was measured using the Connor-Davidson Resilience Scale (CD-RISC-10), with one item removed following pilot testing, resulting in a modified 9-item version, while psychological well-being was assessed using the 18-item Ryff's Psychological Well-Being Scale. Data were analyzed using Spearman's rho correlation. The results revealed a significant positive correlation between resilience and psychological well-being among working sandwich generation individuals in Jabodetabek (ρ = .542, p < .001), indicating a moderate positive association. These findings indicate that individuals with higher levels of resilience tended to report higher levels of psychological well-being. This study provides empirical evidence regarding the association between resilience and psychological well-being among working sandwich generation individuals.